The Implementation Of Multiple Intelligences In High Class Learning At The Stage State Elementary School Kedung District Jepara Regency - Widiyono Aan (IJPSE : Indonesian Journal of Primary Science Education, 2022)
Nur Khomsanah. 2022. Implementation of Multiple Intelligences in High Class Learning at Panggung State Elementary School, Kedung District, Jepara Regency. Bachelor of Education for Elementary School Teachers, Faculty of Tarbiyah and Teacher Training. Nahdlatul Ulama Islamic University Jepara. Supervisor: Muhammad Misbahul Munir, M.Pd. 140. This study aims to describe the implementation, supporting factors, barriers and student responses in applying multiple intelligences-based learning to high-class students at Panggung State Elementary School, Kedung District, Jepara Regency. This research is a qualitative descriptive study. The subjects of this study were teachers and high grade students (grades IV, V and VI). Data collection techniques in this study were observation, interviews, documentation and questionnaires. The data analysis technique in this study uses data reduction steps, data presentation and conclusion drawing. The results showed that the implementation of multiple intelligences-based learning activities consisted of 3 stages, namely initial activities, core activities and closing activities. In the initial activity, apperception and motivation were given. The apperception and motivation are in the form of alpha zone activities, warmer, pre-teaching and scene setting. While in learning activities students are facilitated to learn through the eight types of intelligence, namely: linguistic, logical-mathematical, spatial-visual, kinesthetic, musical, interpersonal, intrapersonal and naturalist. Learning assessment is done authentically. The supporting factor in implementing multiple intelligences-based learning is teacher competence. The obstacles experienced in implementing multiple intelligences-based learning are students. Student response data in this study were taken from student response questionnaires and can be categorized as very good student responses to multiple intelligences-based learning. Keywords: Implementation of multiple intelligences in learning